Advances in Smart Prosthetics: A Focus on Prosthetic Arms - Hameed, Aya Majeed; Ali, Zainab Majeed; Jasem, Nabaa Saad; Hamodi, Ammar Faris (Journal of Science in Medicine and Life, 2025)
The field of smart prosthetics has witnessed significant technological advancements in recent years, offering new possibilities for individuals who have lost limbs or have congenital limb deficiencies. Among the most notable developments is the prosthetic arm, which has evolved from simple mechanical replacements to sophisticated, biomechanical systems capable of mimicking human limb functions. This research paper explores the evolution of smart prosthetic arms, with a particular focus on their design, functionality, and integration of advanced technologies such as brain-computer interfaces, artificial intelligence, and sensory feedback mechanisms. The paper also highlights key research examples, including breakthroughs in myoelectric control, haptic feedback, and neural integration, which contribute to improved performance and quality of life for prosthetic users. The ultimate goal of these innovations is to enhance the functionality, comfort, and intuitive control of prosthetic limbs, moving towards a future where artificial limbs become truly integrated into the human body.